Self-pickup or door-to-door: The impact of self-pickup service on e-tailers. Issue 6 (3rd October 2017) - Liu, Chang; Xie, Bing-Lei; An, Shi
Abstract: Bearing heavy burden on logistics costs, e-tailers in China recently allow consumers to pick up packages themselves at the designated sites. This essay develops a stylized model based on Hotelling Model and study how consistent and inconsistent pricing strategies vary with e-tailer's profit and consumer's purchase decisions. The analysis demonstrates that adding self-pickup scenario avails e-tailer to obtain more profits, and e-tailer performs better when setting price differentiation for two scenarios.